2015
DOI: 10.1038/bmt.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Related hematopoietic cell donor care: is there a role for unrelated donor registries?

Abstract: In almost half of allogeneic hematopoietic progenitor cell (HPC) transplants, a related donor (RD) is used, yet a lack of standardized guidelines means that their care is heterogeneous. Changes to regulatory standards aim to improve uniformity, but adherence to these regulations can prove logistically difficult for the transplant centers (TCs) managing RDs. Discussion has ensued around possible alternative models of related donor care and a session at the European Society for Blood and Marrow Transplantation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The decline in BM as a cell source for adult‐related donor transplants is such that transplant physicians entering the field now are unlikely to gain sufficient exposure to become experts in BM harvesting outside the largest transplant centers. Solutions to this problem require consideration by the transplant community; for example, in the Netherlands this has been addressed by UD registry–affiliated collection centers performing BM harvests for both related and UDs …”
Section: Discussionmentioning
confidence: 99%
“…The decline in BM as a cell source for adult‐related donor transplants is such that transplant physicians entering the field now are unlikely to gain sufficient exposure to become experts in BM harvesting outside the largest transplant centers. Solutions to this problem require consideration by the transplant community; for example, in the Netherlands this has been addressed by UD registry–affiliated collection centers performing BM harvests for both related and UDs …”
Section: Discussionmentioning
confidence: 99%
“…For example, studies reported that donors thought meeting with the transplant team prior to donation was helpful but failed to provide any further detail regarding the content and delivery mode of the information provided. The issue which remains is whether any parallels can be drawn between the management of related HSC donors as mentioned in the literature and current recommendations and guidelines for the care of related HSC donors (Anthias et al, ; Clare et al, ; O’Donnell et al, ; Van Walraven et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Situation of conflicts of interest (a member of the medical team engaged in both donation and transplantation), the lack of standardized clinical eligibility criteria and of centralization of adverse event, and donor follow-up reporting system are challenging points [56]. …”
Section: Donor Selectionmentioning
confidence: 99%